Modeling Communication with Robots and Virtual Humans Second ZiF Research Group 2005/2006 International Workshop on Embodied Communication in Humans and Machines, Bielefeld, Germany, April 5-8, 2006, Revised Selected Papers - Wachsmuth, Ipke; Knoblich, Günther (Lecture Notes in Artificial Intelligence, 2008)
Two main types of embodied agents are playing an increasingly important role in cognitive interaction technology: virtual humans inhabiting simulated environments and humanoid robots inhabiting the real world. The need to develop an integrated perspective of embodiment in communication, establishing bridges between lower-level, sensorimotor functions and a range of higher-level, communicative functions involving language and bodily action has led to the exploration of how artificial agents can advance our understanding of key aspects of embodiment, cognition, and communication. The 17 articles in this state-of-the-art survey address artificial intelligence research on communicative agents and also provide an interdisciplinary perspective from linguistics, behavioral research, theoretical biology, philosophy, communication psychology, and computational neuroscience. The topics include studies on human multimodal communication; the modeling of feedback signals, facial expression, eye contact, and deception; the recognition and comprehension of hand gestures and head movements; communication interfaces for humanoid robots; the evolution of cognition and language; emotion and social appraisal in nonverbal communication; dialogue models and methodologies; theory of mind and intentionality; complex systems, dynamic field theory, and connectionist modeling.